Empowerment of The Community Health Workers in Management of Posbindu for Non-Communicable Deases in Sukamentri Village, Garut Kota District, Garut Regency - Udin Rosidin; Dadang Purnama; Iwan Shalahuddin; Nina Sumarni; Umar Sumarna; Rohmahalia M Noor (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Non-communicable diseases are currently a major health problem and the biggest cause of death in the world. This problem arises is caused of the behavior of the people who do not understand how to prevent it. The right prevention strategy is to utilize the service an facility is aimed at integrated human development that called Posbindu, especially posbindu for non-communicable diseases. In order that the posbindu non-communicable diseases  of to function properly, it requires the ability of community health worker to manage the posbindu non-communicable diseases in each hamlet in a village. The purpose of this activity is to increase the knowledge and ability of community health worker in managing posbindu non-communicable diseases. The target of the councelling is community health worker in 1th Hamlet to 7th Hamlet Sukamentri Village, Garut Kota district, Garut Regency. The activity is carried out in two days starting on May 17th until 24th, 2022. The stages of the activity consist of social and administrative preparation, implementation and evaluation of activities. Preparation is done by conducting an survey to see the community health problems. Implementation is done through health education and training. The activities went well according to plan. The results of the activity showed an increase in knowledge and skills of the community health workers in managing posbindu non-communicable diseases. Implementer of the activity is the councelling team consisting of lecturers, Guntur  Community Health Center and the students at Padjadjaran University.